Continuous Improvement Post Organizational Changes in the Official School of Meteorological, Climatological and Geophysical Agency - Ita Soegiarto; Billy Tunas; Muhammad Yasin (IJHCM (International Journal of Human Capital Management), 2019)
As we know that there are some of vocational educations that have official ties with ministries or ministry-level bodies, one of them is the College of Meteorology, Climatology and Geophysics. The purpose of this study is to find things to improve the organization after changes. The main question that guides this research is the sustainability effort that needs to be applied and influences the organization. Research uses qualitative methods and case study approaches. The sampling technique was purposive and snowball sampling with 40 informants. Based on the research that has been done, found that improvements must be made continuously after organizational changes are divided into two factors. Internal factors such as lecturer competency, lecturer availability, and additional composition in the teaching-learning process from theory to practicum. While external factors regularly review of curriculum and syllabus, technology updates, and digitalization. The update in this study, each lecturer is required not only in the transfer of knowledge but also to instill ethical and moral values. The cadets were prepared as agents of change. As an official school, each graduate not only understands the knowledge gained during education but also must be ready to work at the parent institution. The cadets must be well prepared to work at the Meteorology, Climatology and Geophysics Agency. For this reason, the things that need to be done in maintaining sustainability after the change in the official school organization are updating technology. There needs to be "digital culture" in various activities at STMKG, comparative studies, and participation in national and international seminars so that continuous learning and continuous improvement are always rolling.